Opinions of high school students in central Elazig about elderliness - Oguzoncul, A. Ferdane; Aygen, Murat; Acik, Yasemin; Deveci, S. Erhan; Demirbag, B. Canan; Pirincci, Edibe (Dove Medical Press Ltd, 2015)
Methods: Students attending five different types of high schools in central Elazig (a city in Turkey) during the 2009-2010 school year constitute the study population. One class was randomly selected from each high school. Out of 650 students, 640 participated in the study. The data were evaluated by using the SPSS program; percentage, mean, and chi-square analyses were used. Findings: Of all the students, 41.7% defined the elderly as those who are 60 years of age or older. When asked the question What does elderliness mean to you?, the majority of the students, 27.2%, responded peace and resting. The second most common answer, given by 23.6% of students, was sickness/tiredness; 16.6% responded wisdom/experience. Many students (30.3%) stated that the most difficult thing about living with the elderly was their interference in everything; 30.6% of students stated that there was no difficulty at all. According to 42.7% of the students, the greatest problem that the elderly face is health. Of all of the students, 58.3% stated that they feared growing old. Conclusion: Our study has concluded the following: 1) High school students have a conventional perception of elderliness and 2) They embrace the elderly and think that perspectives on elderliness will change through education.
Keywords: old age; elderly; high school students; opinion